PELANGGARAN-PELANGGARAN YANG DAPAT DILAKUKAN OLEH NOTARIS DAN PEJABAT PEMBUAT AKTA TANAH (PPAT) SEHINGGA BERIMPLIKASI AKTA KEHILANGAN KEOTENTISITASANNYA - , Mulyana, SH; , Prof. Dr. Abdul Ghofur Anshori, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study goal is to find how form of Notary and PPAT responsibility for making the certificate authentic, what are deviations of the Notary and PPAT so that they lost authentic of certificate they made, and how the Notary and PPAT were responsible for loss of certificate authentic. This study, concerning Notary and PPAT responsibility for making certificate authentic, is juridical-empirical using primary data collectible directly from society, supported by secondary data, law rules regulating Notary and PPAT Jobs. The selected location is Payakumbuh city and Lima Puluh Kota district. Sub-district leader were PPAT, whereas two individuals of three sub-district leaders existing in Payakumbuh. Two notary individuals of three notary individuals and five notary individuals and PPAT individuals of 7 notary individuals and PPAT individuals existed in Payakumbuh city and Lima Puluh Kota district. Form of Notary and PPAT responsibility for making certificate authentic could be seen in UUJN of Article 16, regulating duty of Notary, if the Notary did not perform their duty as specified in Article 16 of paragraph (1), Points A â K, then to the involved Notary was incurred by administrative sanction as regulated in Article 84 of UUJN